A relação do professor com o saber no ensino remoto mediado pelas novas tecnologias digitais: a formabilidade do sujeito biográfico - Rodrigues, Fabiana da Silva Santos (Universidade Federal de São Carlos, 2023)
Due to the suspension of classes in 2020 by virtue of the Covid-19 pandemic, many teachers, including those working in Basic Education, were compelled to carry on with classes while deprived of school premises. Emergency remote teaching were the alternative chosen to continue the school year, demanding, to a certain extent, the use of new digital technologies to aid pedagogical practices and communication with students and parents. In this context, this study had the general objective of analyzing and comprehending the teacher’s relationship to knowledge with new digital technologies used due to the suspension of in-person classes and the adoption of distance learning. Our research was underpinned by two theoretical perspectives: Bernard Charlot’s theory of relationship to knowledge and Delory-Momberger’s theory of biographization, both being used as research tools and for data analysis. With regards to the methodology employed in the development of this study, we opted for qualitative biographical research interviews, based on the works of Delory-Momberger, which stand out for addressing the relationship between life, school, the formative process and self-education. Being developed from a perspective that looks at life stories, five early childhood educators working for the public sector in the city of Hortolândia - SP, Brazil, were interviewed. Educational research, on the other hand, brings us relevant contributions about the teacher’s knowledge, who reaches the core of the relationship to knowledge, while also pointing to other aspects of human life. From this point of view, the results point to a relationship between the teacher’s knowledge and the domain of various education actors during this period of emergency remote teaching. The biographical narratives of the teachers interviewed in this dissertation, inscribed in the dynamic of a personal project, reveal reflection and action through experience, shedding light on the concepts of reflective narratives and the formation of the biographical subject. Lastly, the theoretical perspectives about relationship to knowledge and biographization that guided this study raise elements that can contribute to new ways of thinking about education, paving the way for the advent of the Other School.
The teacher's relationship with knowledge in remote education mediated by new digital technologies: the formability of the biographic subject
Keywords: Relação com o saber; Biografização; Educação; Tecnologia; Relationship to knowledge; Biographization; Education; Technology; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO